PENGARUH KEPEMIMPINAN, KOMPENSASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. AERO INDONESIA - Anita Fatimatuz Zahroh; Maulidyah Amalina Rizqi (Journal of Management and Creative Business, 2023)
Human Resources (HR) is a central factor in an organization, which has an important role in the company as a driving factor, planning and controlling in all company activities. Therefore it is necessary to pay attention and create effective and efficient work, organization. This study aims to determine the effect of leadership, ethics and discipline on employee performance at PT. Aero Indonesia. This type of research used is quantitative research. The sampling technique used a saturated sample with a total sample of 72 respondents. The population used in this research is all employees of PT. Aero Indonesia. The data analysis technique used in this study is a multiple linear method. From the calculation results show that leadership (X1), sensor (X2), and discipline (X3) have a significant effect on performance (Y) at PT. Aero Indonesia